Parish revival in Southern Russia in the context of revolutionary upheavals and the Civil War - Yu. A. Biryukova (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the problem of parish reform in the period of revolutionary processes and the beginning of the Civil War in the South of Russia. The author analyses the church-public perception of the position, functions and role of the parish in the church, public and political life through the prism of the discussion which took place on the eve and during the All-Russian Local Council of 1917– 1918 and appeared in church periodicals. One can trace the process of the parish revival and the acceptance of the sobor solution to the parish problem by the ecclesiastical community of Southern Russia. Church revival was connected to a revival of the parish on the basis of sobor-canonical principles, with the first Christian community serving as its ideal. The main activity on this path was the formation of parish councils, the activity of which went far beyond the inner boundaries of the parish. Its functions were to be extended to the level of a grass-roots zemstvo, to ensure the legal and economic security of the parishioners, and to influence the surrounding society.